Wheat leaf lipids during heat stress: II. Lipids experiencing coordinated metabolism are detected by analysis of lipid co‐occurrence. (21st December 2015) - Narayanan, Sruthi; Prasad, P.V. Vara; Welti, Ruth
Abstract: Identifying lipids that experience coordinated metabolism during heat stress would provide information regarding lipid dynamics under stress conditions and assist in developing heat‐tolerant wheat varieties. We hypothesized that co‐occurring lipids, which are up‐regulated or down‐regulated together through time during heat stress, represent groups that can be explained by coordinated metabolism. Wheat plants ( Triticum aestivum L.) were subjected to 12 days of high day and/or night temperature stress, followed by a 4‐day recovery period. Leaves were sampled at four time points, and 165 lipids were measured by electrospray ionization‐tandem mass spectrometry. Correlation analysis of lipid levels in 160 leaf samples from each of two wheat genotypes revealed 13 groups of lipids. Lipids within each group co‐occurred through the high day and night temperature stress treatments. The lipid groups can be broadly classified as groups containing extraplastidic phospholipids, plastidic glycerolipids, oxidized glycerolipids, triacylglycerols, acylated sterol glycosides and sterol glycosides. Current knowledge of lipid metabolism suggests that the lipids in each group co‐occur because they are regulated by the same enzyme(s). The results suggest that increases in activities of desaturating, oxidizing, glycosylating and acylating enzymes lead to simultaneous changes in levels of multiple lipid species during high day and night temperature stress in wheat. Abstract : Identifying lipids that experience coordinated metabolism during heat stress would provide information regarding lipid dynamics under stress conditions and assist in developing heat‐tolerant wheat varieties. We found that co‐occurring lipids, which are up‐or‐down‐regulated together through time during high day and night temperature stress, represent groups that can be explained by coordinated metabolism. Current knowledge of lipid metabolism suggests that the lipids in each group co‐occur because they are regulated by the same enzyme(s). The results indicate that increases in activities of desaturating, oxidizing, glycosylating, and acylating enzymes lead to simultaneous changes in levels of multiple lipid molecular species during high day and night temperature stress in wheat.